National Resilience in Historical and Geostrategic Perspectives: Essence and Conception - Muthia Salsabila; Zaenul Slam; Mutiara Nur Alamsyah; Hifzah Dwi Hilmi (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: To analyse how historical and geostrategic perspectives influence Indonesia's national resilience in overcoming domestic and global challenges. Study Design/Methodology/Approach: A qualitative descriptive-analytical method was applied by examining historical records, constitutional principles, and geostrategic frameworks related to resilience. Findings: Indonesia's resilience integrates ideology, politics, economics, socio-culture, and defence. Pancasila serves as ethical guidance, the 1945 Constitution establishes legal frameworks for security, and Archipelago Insights provide a unified geopolitical vision. Historical events confirm Indonesia's ability to resist colonialism and internal conflicts. Collaboration among societal elements is essential to counter shocks and sustain national stability. Originality/Value: This research provides a comprehensive view of resilience through historical and geostrategic lenses. It highlights the importance of cooperation across all sectors to strengthen resilience and recommends further exploration of how hate speech affects national cohesion.